Effect of water storage on the shear strength and fatigue limit of the reline resin bond to denture base resins - Vergani, Carlos Eduardo [UNESP]; Seo, Rosangela Seiko; Santos Nunes Reis, Jose Mauricio; Giampaolo, Eunice Teresinha; Pavarina, Ana Claudia [UNESP]; Machado, Ana Lucia [UNESP] (Quintessence Publishing Co Inc, 2010)
Purpose: This study evaluated the effect of water storage (WS) on the shear bond strength (SBS) and shear bond fatigue limit (SBFL) between denture base and reline resins. In addition, a possible correlation between SBS and SBFL was evaluated.Materials and Methods: Two denture base (Lucitone 550-L and Acron MC-AC) and two reline resins (Ufi Gel Hard-UGH and Tokuso Rebase Fast-TR) were selected. Cylinders (20 x 20 mm) of each denture base resin were processed, and the reline resins were packed on the bonding surfaces using a split mold (3.5 x 5.0 mm). Specimens of each denture base-reline resin combination were subjected to shear forces (0.5 mm/min) until fracture. A staircase approach was used to determine the SBFL. Specimens were submitted to either 10,000 cycles (5.0 Hz) or until fracture. For both SBS and SBFL, specimens were tested after relining (control) and after 30 days of WS. Data (MPa) were analyzed with 2-way ANOVA and Tukey's tests (alpha = 0.05). To test for a possible correlation between the SBS and SBFL, a linear regression analysis was performed.Results: WS significantly increased (p < 0.05) the SBS of AC-TR and AC-UGH and the SBFL of AC-TR, AC-UGH and L-UGH. After WS, UGH produced higher (p < 0.05) SBS than TR, regardless of the denture base resin used. Regardless of the experimental groups and the denture base resins used, UGH produced higher (p < 0.05) SBFL than TR specimens. A strong positive linear correlation (r(2) = 0.949) was observed between the SBS and SBFL.Conclusion: Overall, UGH promoted the highest SBS and SBFL. WS increased the SBS and SBFL of the AC relined specimens. A positive correlation was observed between the two variables.
Keywords: shear strength; fatigue limit; water storage; adhesion; acrylic resins; reline resins